HAZARD CONTROL ANALYSIS USING THE HAZARD IDENTIFICATION RISK ASSESSMENT AND RISK CONTROL (HIRARC) METHOD IN THE WORK SAFETY AND HEALTH (K3) PROGRAM IN THE LABORATORY - Widiastiti, Ir. I G. A.A. Mirah (Prosiding Seminar Nasional Sains dan Teknologi (Senastek); Vol 8 No 1 (2023): Senastek 2023, 2023)
Abstract: Work safety is a conditions when people carrying out work in a safe and healthy condition. Occupational health is a condition that ensures a person's body is physically healthy when doing work. The laboratory is one of the learning forums both in college and in high school. Occupational safety and health (K3) is a very important factor to know when carrying out practical activities in the laboratory by students, lecturers, researchers and laboratory staff in preventing work accidents. The phenomenon currently occurring in the field is still a lack of implementation of K3 in laboratories, such as students still rarely using PPE (Personal Protective Equipment) when carrying out activities in the laboratory. This can be overcome by conducting an analysis of the hazard risk control system using the Hazard Identification Risk Assessment and Risk Control (HIRARC) method and optimizing the implementation of occupational safety and health (K3) programs in the laboratory. The aim of this research is to determine the analysis of the hazard risk control system using the Hazard Identification Risk Assessment and Risk Control (Hirarc) method and to achieve optimization of the occupational safety and health (K3) program in the laboratory. The results of the research concluded that hazard identification had been carried out with a risk assessment of activities with 58% of low risk (low risk), 34% of medium risk (moderate risk), 8% of high risk (high risk) and 0% of very high risk (extreme risk). Keywords: Laboratory, HIRARC Method, Occupational Health and Safety (K3)